A "tottering lace-like architecture of ruins”: the wartime home in Elizabeth Bowen’s The heat of the day - Zimmerman, Emma (2015)
Elizabeth Bowen’s The Heat of the Day (1949) is a novel permeated with the architectural ruins of the Second World War. This article is concerned with the shock effects the war had on Bowen’s understanding of the material world and the resultant implications for the late modernist narrative strategies she employs in The Heat of the Day. Drawing on theoretical understandings of space and place from cultural geography, I focus critical attention on the marked materialities of the novel. I consider the extent to which Bowen’s representation of the domestic interior resists the notion of the Heideggerian dwelling place and instead exposes the stark deracination of the wartime individual. I also draw connections with the strained, disjunctive style of the narrative – a style that Bowen (1950) explains is ‘to a certain extent intended. I wanted […] a smashed up pattern with its fragments invecting on one another’ (238) – arguing that it shares continuities with the stylistic anxiousness of early modernism. Bringing these points of focus into dialogue with recent debates about wartime literature and the periodization of modernism, I show how Bowen (re)constructs, out of the wartime ruins, a deeply unsettling late modernist portrait of the fractured domestic landscape of 1940s London.